Swahili Forum im 10. Jahr – nun online - Geider, Thomas (AAeO - Afrikanistik-Aegyptologie-Online, 2005)
The steady growth of research, teaching and publishing over the last twenty years on all continents has made Swahilistics a well established and much differentiated sub-discipline within African studies. Its object is the study of the language, literature, society, culture and history of the Swahili-speaking populations in East Africa and the diaspora and the usage of the language in transnational institutions and the internet.